Displaced commercial risk in Islamic banking institutions in Malaysia / Noraziah Che Arshad - Noraziah , Che Arshad (2017)
Islamic banks are exposed to a unique risk such as Displaced Commercial Risk (DCR). DCR arises from the assets managed on behalf of the investment account holders which may be borne by the Islamic bank’s own capital, when the Islamic banks forgo part or all of its share of profits on the investment account holders funds, in order to increase the return to the investment account holders. In a dual banking system, DCR could be a threat to the Islamic banks given the competition of fixed and higher return from the conventional banks. However, DCR would not be a threat to Islamic banks if their account holders choose Islamic banks due to religious obligatory factor. The difficulty for the banks, then, is how to estimate or measure this DCR and how much capital they to set aside to protect against such exposure. Based on the Islamic Financial Services Board (IFSB), in particular the Capital Adequacy Standard (CAS), the Central Bank of Malaysia used the standardized approach capital adequacy guidelines in the context of Islamic practices. However, there are some weaknesses in using this approach and significant efforts need been made to design a more appropriate capital regulation for Islamic banks. The regulator would not be able to determine a standard ratio for Islamic banks generally as it depends on a myriad of banks’ specific characteristics such as to what extent they will agree to absorb the losses and the availability of historical data on the performance of their assets. We propose the Value at Risk (VaR) model as an alternative method to measure the additional capital charges required to cover the displaced commercial risk. Pertaining to this issue, this research aims to analyse the determinants of DCR and to examine the impact of DCR on Islamic bank performance. We find that DCR is one of the factors that affect bank performance on both profitability and stability, at least in the case of Malaysian Islamic banks. This empirical evidence implies that Islamic banks operating in a dual banking system are adversely affected by DCR. The results draw the attention of the Islamic banks and regulators on the need to improve the level of understanding among the Islamic banks’ customers regarding the nature of return that is to be expected from Islamic deposits. Since displaced commercial risk is due to floating depositors.